PENERAPAN STRATEGI PEMASARAN, DIGITAL MARKETING MELALUI E-COMMERCE DAN MARKETPLACE UMKM TOAPAYA UTARA - Imran Ilyas; Masyitah As Sahara; Aulia Dewi Gizta; Framugia Cahyo Laksono; Aldi Kurniawan; Rofi Khotullumah Hersadillah; Pramuditha Febriani; Dicky Yusuf Sinambela; Dinda Venna Hendryany; Shakilla Dwi Maharani Sucahyo; Lailatul Jamilah; Erik Setiawan; Muh.Bagas Prayuda; Deri Ihza Saputra; Shalsabilla Nawra; Dhea Annisa; Siti Melinda; Sherly Chang; Meilin Lorensia; Rizki Atu Mofida; Erika Amanda Rheta; Yanah Yanah; Fiona Fiona; Isihati Telaumbanua (Bajang Institute, 2023)
Empowerment Activities Are A Form Of Community Service By Group 17 KKN Of The Tanjungpinang Development Economics College (STIE). Empowerment Activities Through Assistance For MSME Actors, Along With The Development Of Technology And The Need For Information, The Internet Is Also Experiencing Development. So Currently, A New Pattern Appears In Doing Business Processes That Is By Using The Internet. In Today's Business, Marketplace Or E- Commerce Is One Of The Places To Promote Products To Be More Efficient, Flexible, And Can Save Costs. The Non-Profit Partners In This Activity Are Micro, Small And Medium Enterprises (Msmes) That Produce Sweet Potato Rengginang In North Toapaya Village. This Business Has Been Established Since 2007 In North Toapaya Village, It Has Been About 15 Years That This Business Has Been Going On, But The Marketing Is Still Very Minimal, MSME Actors Still Need To Understand The Importance Of Using Digital Marketing To Improve The Marketing System So That They Can Expand Their Business Goals And Can Support Activities. Sales For Better. The Results Of This Service Are Expected That MSME Actors Can Understand The Importance Of Understanding Digital Marketing In Marketing Their Product.